Kenya today breaking the yoke of colonialism in Africa - Mwaura, Ndirangu; ebrary, Inc. (New York : Algora Pub., 2005)
"Examining the impact of foreign aid, trade policies, study-abroad programs, religion, entertainment, the media and other forms of foreign influence on Kenya and other under-developed African nations, the author finds that initiatives billed as "assistance" in many cases serve instead to keep in place the colonial status of dependency"--Provided by publisher.
pt. 1. Factors hindering development -- pt. 2. How neocolonialism is sustained.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Economic assistance -- Kenya; Technical assistance -- Kenya; Kenya -- Colonial influence; Kenya -- Relations; Electronic books